PENGARUH KINERJA KEUANGANPERUSAHAANTERHADAP PEMBERIAN OPINI AUDITGOING CONCERN - Kurnia, Indrawan Joko (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out whether profitability, liquidity, and solvability have significant influence to the provision of going concern audit opinion. The SPSS.20 statistics test instrument is used to carry out logistic regression analysis. The logistic regression analysis model shows that profitability has positive significant influence to the provision of going concern audit opinion, liquidity has negative and insignificant influence to the provision of going concern audit opinion, and solvability has positive and insignificant influence to the provision of going concern audit opinion.Keywords: profitability, liquidity, solvability, going concern audit opinion.